2019
DOI: 10.3991/ijet.v14i23.11433
|View full text |Cite
|
Sign up to set email alerts
|

A Tangible User Interface to Facilitate Learning of Trigonometry

Abstract: In mathematics education, studies reveal difficulties in the teaching-learning of trigonometry in secondary and higher education, due to the fact that students are not encouraged to achieve a deep conceptual understanding of abstract concepts. Several studies demonstrate that incorporating digital technologies has a positive impact on students’ learning. However, most of the existing technologies do not consider the use of the body and multiple senses. Tangible User Interfaces (TUIs) in contrast, can host bodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
4
5
0
1
Order By: Relevance
“…With respect to understanding equation-solving concepts, our findings are in line with those of other studies [14,43,45] that found that TUIs are likely to assist students in developing their understanding of mathematical concepts. We found that X-is could benefit diverse-attaining pre-primary through ninth-grade students in understanding equation concepts.…”
Section: Discussion Of Learning Supportsupporting
confidence: 91%
See 4 more Smart Citations
“…With respect to understanding equation-solving concepts, our findings are in line with those of other studies [14,43,45] that found that TUIs are likely to assist students in developing their understanding of mathematical concepts. We found that X-is could benefit diverse-attaining pre-primary through ninth-grade students in understanding equation concepts.…”
Section: Discussion Of Learning Supportsupporting
confidence: 91%
“…Particularly, their argumentation indicated that they had a good understanding of mathematical equivalence (e.g., the equal sign as a relational symbol) and the equation-solving process. The evidence that X-is is advantageous for students' learning achievement corroborates the findings of earlier work [14,45,81] in tangible technology-enhanced mathematics learning. Moreover, the findings from the thinking aloud data suggest that X-is facilitated the achievement of equation learning (i.e., modelling and solving equations successfully) among diverse students, particularly low and medium achievers.…”
Section: Discussion Of Learning Achievementsupporting
confidence: 86%
See 3 more Smart Citations